Survival Mechanism of Puccinia abrupta var. partheniicola Urediniospores During Summer Season - MOHAMAD TAUFIK FAUZI (Indonesian Society for microbiology, 2009)
The success of applying plant pathogens as biological control agents of weeds relies on the ability of the biological control agent to persist at all parts of the year and to successfully go through all of its life cycle stages in the course of a single year. One important aspect of any plant disease life cycle is the ability to survive during unfavorable parts of the season. The research aimed at understanding the mechanism involved in the survival of Puccinia abrupta var. partheniicola, a potential biological control agent of parthenium weed (Parthenium hysterophorus), during simulated summer conditions had been undertaken in the field plot at the Alan Fletcher Research Station, Brisbane. The urediniospores that were placed either on plant debris or on intact plants were exposed to summer conditions and were regularly tested their viability after being exposed. The results showed that the urediniospores could only survive for less than six weeks, which is less than half of the Queensland summer where the weed is abundant. This indicates that the rust spores do not survive on infected parthenium weed debris during summer season.